Friendship quality of adolescents, who are inclined and who are not inclined into delinquent behavior, comparision - Blažytė, Violeta; Raižienė, Saulė (Pedagogika, 2014)
Using a longitudinal sample this study aim was to compare friendships quality with the best friend and the amout of friends of adolescents who are inclined into delinquent behavior and who are not inclined into delinquent behavior. The sample consisted of 2638 adolescents: 1482 boys (56.18 %) and 1156 girls (43.82 %). Respondents were divided into goups of boys and girls who are inclined into delinquent behavior and who are not inclined into delinquent behavior. Friendship quality was assessed by free J. G. Parker and S. R. Asher (1989) Friendship Quality Questionaire subscales: 1) Validation and Caring scale, 2) Intimate Exchange scale, 3) Conflict and Betrayal scale. Delinquent behavior was assessed by problematical behavior scale evaluation, which was created by the group of project “Political socialization development from the adolescence till the youth: mechanisms of citizens political identity development in Lithuania” researchers according to B. Kracke and M. Held (1994). Amount of adolescents’ intimate friends was assesed by asking respondents to write up to 8 friends names and surnames from the school. Research results show that boys are more inclined into delinquent behavior than girls. Friendships with the best friend of adolescents who are inclined into delinquent behavior are more intimately exchangeable and conflicted then friendships with the best friend of those adolescents who are not inclined into delinquent behavior. Validation and caring level of adolescents, who are inclined into delinquent behavior and who are not inclined into delinquent behavior, friendships do not differ. Furthermore, adolescents who are inclined into delinquent behavior have more friends than adolescents who are not inclined into delinquent behavior. This research shows that friendships of adolescences twho are inclined into delinquent behavior has some similarities and some differences from the friendships of adolescences who are not inclined into delinquent behavior.